SKI-ERG training for enhancing anaerobic glycolysis in cross-country skiers - Bakhareva, A. S.; Aminov, A. S.; Latypova, E. F.; Savinykh, E. Y.; Cherepanov, V. S. (Journal of Physical Education and Sport, 2021)
The aim of the study was to determine the effectiveness of the cross-country ski training method based on the development of anaerobic glycolysis. Materials and methods. The study involved a highly skilled skier (27 years old). To assess the effectiveness of training for the development of anaerobic glycolysis, the subject was asked to perform two training sessions on the SkiErg ski ergometer with double pole technique with an interval of 16 days. The training protocol consisted of 8 sets of 30 seconds after a 5-minute rest. The first set was performed as a warm up, the rest were performed at a power of about 70-80% of the maximum alactate power (MAP). The power of physical activity was set and regulated by the PerfPro computer program developed to work simultaneously with ergometers according to the ANT + system (Fig. 1). After each set, at the end of the first minute of rest, the concentration of lactate was measured using the LACTATE PLUS portable device(USA). According to the results of the study, the indicators of power, capacity and efficiency of anaerobic glycolysis were calculated. Power was evaluated by the rate of lactate accumulation (La (mmol/L/30 s). The capacity of anaerobic glycolysis was assessed by the maximum accumulation of lactate in the blood. Theefficiency of anaerobic glycolysis was assessed by the ratio of lactate concentration to the length of the distance (La/S, (mmol / m)). The study was carried out at the pre-competitive stage. Results: The training method on the ski ergometer, which comprises 8 sets of 30 seconds after a 5-minute rest, was a local work for the development of anaerobic glycolysis. Power indicators increased by 50.16% (p <0.05), efficiency - 48.25% (p <0.05), capacity - 32.32% (p <0.05). Conclusion: The method proposed can be considered as a specific work for the development of speed endurance and anaerobic glycolysis, the inclusion of which is possible only under the condition of a formed "aerobic base." It aims to avoid excessive accumulation of metabolites due to local work, which allows to control the power drop. The efficiency of glycolytic performance 8x30 sec consists in the following protocol: the number of sets is not more than 8; stop criterion is a drop in average power by 5-7%, rest between sets for at least 5 minutes; determining blood lactate from finger blood, the difference between earlobe blood is about 1.5 mmol; the first set is warming up, the rest should be conducted at a power of about 70-80% of the MAP (maximum alactate power).